The Approach to Fire Safety in the Curriculum Map-Matrix of Engineering Courses at a Federal University According to the Parameters of Law 13.425: A Systematic Review (Global Journals of Research in Engineering, 2022)
Fire protection has gained the spotlight in large part as a result of some disasters that have occurred in recent years The subject has evolved and gained considerable prominence thus requiring changes in current legislation as well as the formulation of new Standards and Laws capable of mitigating the risk of fire occurrence It is necessary to understand the role of the future engineer on the fire protection policy to avoid possible fire occurrences in institutions Therefore the goal of this study is to analyze how and how often the fire protection approach is included in the curriculum of engineering courses To achieve it a systematic review in the Google Academic Scielo and Eric databases was carried out in a quantitative analysis Secondly in a qualitative analysis a case study was carried out starting with an investigation of the curriculum of nine engineering courses at a Brazilian university to verify the consistency of the fire protection approach and compliance with the Kiss Law in the courses studied The results indicate a certain insufficiency of disciplines when analyzing the curricular matrices of each course In most cases the adoption of contents or disciplines that address the topic present fire protection generically and inconsistently It is concluded that there is still a lack of knowledge about the relevance of the topic and effective non-compliance with legislation on the subject There is therefore a need for implementation measures in the learning topics of engineering curricula
Keywords: fire safety kisslaw engineering courses curricular structures